Reversal of the ΔdegP phenotypes by a novel rpoE allele of Escherichia coli. - Owen P Leiser; Emily S Charlson; Henri Gerken; Rajeev Misra (PLoS ONE, 2012)
RseA sequesters RpoE (σ(E)) to the inner membrane of Escherichia coli when envelope stress is low. Elevated envelope stress triggers RseA cleavage by the sequential action of two membrane proteases, DegS and RseP, releasing σ(E) to activate an envelope stress reducing pathway. Revertants of a ΔdegP ΔbamB strain, which fails to grow at 37°C due to high envelope stress, harbored mutations in the rseA and rpoE genes. Null and missense rseA mutations constitutively hyper-activated the σ(E) regulon and significantly reduced the major outer membrane protein (OMP) levels. In contrast, a novel rpoE allele, rpoE3, resulting from the partial duplication of the rpoE gene, increased σ(E) levels greater than that seen in the rseA mutant background but did not reduce OMP levels. A σ(E)-dependent RybB::LacZ construct showed only a weak activation of the σ(E) pathway by rpoE3. Despite this, rpoE3 fully reversed the growth and envelope vesiculation phenotypes of ΔdegP. Interestingly, rpoE3 also brought down the modestly activated Cpx envelope stress pathway in the ΔdegP strain to the wild type level, showing the complementary nature of the σ(E) and Cpx pathways. Through employing a labile mutant periplasmic protein, AcrA(L222Q), it was determined that the rpoE3 mutation overcomes the ΔdegP phenotypes, in part, by activating a σ(E)-dependent proteolytic pathway. Our data suggest that a reduction in the OMP levels is not intrinsic to the σ(E)-mediated mechanism of lowering envelope stress. They also suggest that under extreme envelope stress, a tight homeostasis loop between RseA and σ(E) may partly be responsible for cell death, and this loop can be broken by mutations that either lower RseA activity or increase σ(E) levels.